Predicting revolt: fragility indexes and the level of violence and instability in the Arab Spring - Buterbaugh, Kevin Neil (Terrorism and political violence, 2017)
This article is one of the first to systematically assess the ability of state fragility measures to predict violent protests and adverse regime changes in countries. We focus on the Arab Spring as an example of a situation that such measures ought to predict. Through a variety of analyses, we find that none of the measures are predictive. We then create a simple model using the literature of protest and revolts to predict both the level of violence and the extent of regime change in the Arab Spring countries. This simpler model does a better job of predicting the level of involvement in the Arab Spring than any of the complex State Fragility Indexes. Thus, the goal of this article is not to explain the causes of the Arab Spring, but to add to the discussion of the predictive value of measures of instability.